1st International Conference of Animal Science and Technology (ICAST) 2018. (March 2019) - Unknown
Abstract : PREFACE The 1 st International Conference of Animal Science and Technology (ICAST) 2018 was held in Makassar, Indonesia on November 6 – 7 th 2018 hosted by Faculty of Animal Science Hasanuddin University. ICAST 2018 held with purpose to encourage the importance of local Indonesian livestock in an international event. Furthermore, the livestock sub-sector could be used as a supporting for regional and national economies. So that it will improve the welfare of Indonesian smallholder farmers. Animal Science Faculty of Hasanuddin University is as one of the higher institution in academic and research in livestock business that contributing in innovation, knowledge and technology of animal science. This conference hopefully contributes to develop the proven technology that appropriate with the tropical environment as well as an indigenous technology and improved technology using local wisdom. The aim of the conference were to support animal production in tropical countries, harmonize the synergy among Academics, Business, and Governments, create international researcher networking in animal science and improve international collaboration research and publication. Professors from Egypt, Malaysia, Thailand, and Philippines were invited to deliver keynote speeches, together with invited speakers from Indonesian Universities. Their presence indicates the concern and role of the researchers, scientists and practitioners in animal production, nutrition, social-economic and animal product technology. We would like to appreciate all authors who have contributed to this proceedings, the conference committee, speakers, attendees, organizing committee and sponsors who support the 1 st ICAST 2018. Hopefully this conference proceeding contributes in innovation knowledge and technology of animal science in tropical environment. Ratmawati Malaka Chair of Organizing Committee ICAST 2018.